Identification of Ethanol in the Urine of Moke Drinkers Based on Variation of Time After Consuming the Beverage - Rahmawati, Rahmawati; Qadri Rasyid, Nur; Suardi, Suardi; Fatmawati, Andi; Ravanelli Bara, Fransesco (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Ethanol can be found in Moke drinks which have quite serious impacts if too much is in the human body, because it can cause various diseases, especially in the liver, because the liver functions as a detoxification of toxins in the body. This study aims to identify ethanol in the urine of Moke drink consumers from Maumere Flores. The research conducted was an experimental study, using the Potassium Dichromate method. The sampling technique was a purposive sampling technique with the criteria of age 25 years and over, male gender, and duration of consumption such as 1 hour, 24 hours, and 48 hours after consuming the drink. The sample of this study was 6 urine samples after consuming moke drinks for 1 hour, 24 hours, and 48 hours. The results of the study showed that ethanol could not be identified in urine more than 24 hours after consumption, which was indicated by the absence of color changes in each moke consumer’s urine within 24 hours and 48 hours shown in tables 1, 2 and 3. Thus, positive results were obtained from 1 hour after consumption, then negative results for 24 hours and 48 hours. So it can be concluded that the ethanol contained in the urine of moke drink consumers cannot survive in the body for 24 hours. Keywords: ethanol, urine, moke consumers, potassium dichromate